Lingkungan Pengasuhan dan Tingkat Perkembangan Anak Usia 4-5 Tahun - Sudirman Sudirman; Sri Ernawati; Wa Ode Sitti Justin; Ahmad Amiruddin; Abdul Malik (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2022)
Skills and intelligence in adulthood are a series of developmental processes that children go through from an early age. In addition, the first five years of life are crucial for a child's further development. The future development of children is closely related to the environment in which children are raised. Therefore, a conducive environment is needed to form independent and quality children. The purpose of this study was to examine the relationship between the parenting environment and the level of child development. The research design used a cross-sectional study, carried out in Betoambari District, Baubau City, Southeast Sulawesi involving 90 mothers and children who were selected by purposive sampling from complete families and had children aged 4-5 years. Data was collected through interviews. Data were analyzed descriptively and multiple regression. The results showed that the quality of the parenting environment had an average index value that was included in the medium category. Most of the children's developmental levels are also in the moderate category. The parenting environment has a positive and real influence on the level of child development.